Dual‐Phasic Carbon with Co Single Atoms and Nanoparticles as a Bifunctional Oxygen Electrocatalyst for Rechargeable Zn–Air Batteries. (20th July 2021) - Li, Jin‐Cheng; Meng, Yu; Zhang, Lili; Li, Guanzhou; Shi, Zhicong; Hou, Peng‐Xiang; Liu, Chang; Cheng, Hui‐Ming; Shao, Minhua
Abstract: The great interest in rechargeable Zn–air batteries (ZABs) arouses extensive research on low‐cost, high‐active, and durable bifunctional electrocatalysts to boost the sluggish oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). It remains a great challenge to simultaneously host high‐active and independent ORR and OER sites in a single catalyst. Herein a dual‐phasic carbon nanoarchitecture consisting of a single‐atom phase for the ORR and nanosized phase for the OER is proposed. Specifically, single Co atoms supported on carbon nanotubes (single‐atom phase) and nanosized Co encapsulated in zeolitic‐imidazole‐framework‐derived carbon polyhedron (nanosized phase) are integrated together via carbon nanotube bridges. The obtained dual‐phasic carbon catalyst shows a small overpotential difference of 0.74 V between OER potential at 10 mA cm −2 and ORR half‐wave potential. The ZAB based on the bifunctional catalyst demonstrates a large power density of 172 mW cm −2 . Furthermore, it shows a small charge‐discharge potential gap of 0.51 V at 5 mA cm −2 and outstanding discharge‐charge cycling durability. This study provides a feasible design concept to achieve multifunctional catalysts and promotes the development of rechargeable ZABs. Abstract : A dual‐phasic carbon nanoarchitecture consisting of a single‐atom phase for oxygen reduction reaction (ORR) and nanosized phase for oxygen evolution reaction (OER) is proposed to boost the oxygen electrode performance for rechargeable Zn–air batteries, showing a small OER‐ORR overpotential difference (0.74 V), large power density (172 mW cm –2 ), a small charge‐discharge potential gap (0.51 V at 5 mA cm –2 ), and outstanding discharge‐charge cycling durability.